Differences In Indonesian And Common Law Legal Traditions And New Paradigm Of Types Of Business Contracts - Dhanudibroto, Handojo (UNIVERSITAS PAKUAN, 2023)
Two legal traditions , Indonesian legal law and common law, are frequently studied by academics and legal practitioners. Without diminishing the importance of other legal traditions such as socialism, marxism, Islamic law, etc., these two major traditions often interact in a global trade process. The common law tradition, or known as the Anglo-Saxon tradition or Westminster tradition, is commonly adopted by commonwealth countries and the majority of states in the United States. Meanwhile, Indonesian law tradition originated from the civil law tradition, also known as the continental or Roman tradition, is the applied official law in Indonesia. The collision of legal tradition differences between the parties can not be avoided, as a result of global trade. The legal system of both traditions is complicated as every element of them should be understood, including the principle, method, sources of law, judicial system, style of the practitioners, duties of the court, and ownership of an object. Due to global trade and legal tradition differences between the parties, the adoption of law, harmonization of business contract, and Court of Arbitration should be the middle grounds used as a final step to settle disputes. The adoption and harmonization of law, especially in a business contract, is not recent in the Law of Indonesia. However, only a few practitioners have learned and understood it. Recently, business contracts have a new paradigm, shifting from a win-lose concept to a formal relation contract. A complex business contract based on win-lose concept is considered to no longer maintain the company “healthy” in the performance and profit of the parties. With this awareness, the paradigm of business contracts is changed by the spirit of empathy, win-win solution, solidarity, and shared interests of the parties.